I'dâd al-Mawâd al-Ta'lîmiyyah li Mahârati al-Kalâm Fî Dhoui al-Madkhal al-Wadzhîfî Fî Maskan al-Khairiyyah Sukorejo Situbondo - Shofwatul Fu’adah (IAIN Madura, 2021)
Learning materials are very important in learning Arabic. But in reality, there are many learning processes that do not use even do not have the right textbooks or teaching materials, like the researcher found in Al-Khoiriyah Ma’hadul Qur’an dormitory Sukorejo Situbondo. This was impacting on their lack of speaking skills, while they have to communicate in Arabic and English everyday as bilingual dormitory. Therefore, they need specific learning textbooks so that teaching and learning activities can be directed correctly, especially the textbooks that can support learning maharah kalam, so they can improve their speaking skills. This study aims to preparation textbooks of maharah kalam using functional approach because students need materials that related with their daily activities and functional verbal expressions. The method of this research was research and development (R&D)